Proporsi Tepung Mocaf dan Tepung Jagung dengan Penambahan Keju Parmesaan Terhadap Karakteristik Sensori dan Keseukaan Pound Cake - Novitasari, Gian; Sutiadiningsing, Any; Sulandari, Lilis; Romadhoni, Ita Fatkhur (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The utilization of local materials in Indonesia, such as mocaf flour and corn flour, is still not optimal, thus requiring innovation in food development. One potential product that can be developed is pound cake, which is popular among the community. This type of research is experimental with 9 treatments, involving two independent variables (the proportion of mocaf and corn flour and the addition of parmesan cheese) and dependent variables (sensory characteristics: color, aroma, taste, texture, and overall liking). Data were collected through observations using organoleptic tests conducted with 35 panelists, and data analysis was performed using (Two-Way ANOVA) followed bby Duncan’s post hoc test. The results indicate that the proportions of mocaf and corn flour with theaddition of parmesan cheese do not signifigantyl affect color characteristics, but they do have a significant impact on sensory characteristics regarding aroma, taste, texture, and overall preference. The best product formulation is A1K2 (80 mocaf flour, 20% corn flour, and 15% parmesan cheese), which yields a golden yellow color, balanced aroma, a harmonious sweet and savory taste, and a soft, moist, and dense texture. The nutritional content / 100 g of formulation A1K2 is 42,7% carbohidrates, 11,08% protein, and 4,86% fat.